Electromobile surface charge alters membrane potential changes induced by applied electric fields. - Gross, D (1988)
The relation between extracellular electric fields and changes in membrane potential that such fields directly induce has previously been described both theoretically and experimentally. It is clearly established that extracellular electric-field-induced membrane potential changes are well described by Poisson's equation of electrostatics. A modification of this simple theory to include effects of the electric-field-induced redistribution of charged cell surface components is introduced and is shown to produce major alterations in calculated membrane potential changes over times of the order of minutes to hours. Implications for biological systems which respond to extracellular electric fields are discussed.